Desenvolvimento de método por CLAE-DAD para determinação de espilantol em Spilanthes acmella (L.) Murray - Santos, Daniele Silva dos (2010)
Spilanthes Acmella (L.) Murray (Asteraceae) is native to South America, popularly known as jambu. This plant is used in Northern Region of Brazil as a condiment in typical dishes such as tacacá and pato no tucupi and has application in traditional medicine to treat toothache, stomatitis and throat diseases. Furthermore, several therapeutic properties have been reported for S. acmella such as antiviral, antibacterial, antiseptic, diuretic, anti-inflammatory and healing agent. Spilanthol is the major constituent from flowers of this species, which is associated with several biological activities: analgesic, larvicide, insecticide, antibacterial, antifungal, etc. Currently, extracts of jambu and spilanthol are also used as ingredients for cosmetic anti-aging. Given the above, this work reports the development of a HPLC-DAD method for determination of spilanthol in samples of S. acmella. This study used samples from accessions of S. acmella (fresh whole plant and its parts: leaves, stems and flowers, fresh and dried) cultivated and collected in the Rural Campus-UFS. The conditions for analysis using HPLC-DAD system Shimadzu LC 20A Prominence were: analytical column Luna ® C18 (250 mm x 4.6 mm, 5 m) Phenomenex, gradient elution using as mobile phase MeOH (B): H2O (A): 85% (A) for 6 min., 85-100% (A) for 1 min., 100% (A) for 5 min.; 100-85% (A) for 1 min.; 85% (A) for 10 min; flow rate 1.0 mL/min, injection volume 20 L and the chromatograms obtained at =230 nm. Spilanthol was used as a reference standard (tr=5.1 min). The method was validated according to RE 899/03 (ANVISA). Linearity was determined by external standard calibration curve (r2=0.9997) and by the standard addition method (r2=0.9995). The limit of quantification and detection were 0.7 and 0.1 g/mL, respectively. The repeatability showed coefficients of variation (CV, %) between 0.21 to 2.85% and the accuracy, expressed as a recovery percentage ranged from 100.2 to 103.3%. The method was applied in 41 samples of S. acmella including samples from genetic improvement. Samples of dried flowers and accession J-05 had the highest content of spilanthol (101.2 g/mL and 120.5 g/mL, respectively). Therefore, this work presents a contribution to the quality control of extracts of S. acmella.